Mike Mulligan and his steam shovel - Burton, Virginia Lee (Boston Houghton Mifflin Harcourt, 1967)
When Mike Mulligan and his steam shovel, Mary Anne, lose their jobs to the gasoline, electric, and diesel motor shovels, they find a new opportunity in a very surprising place.
Keywords: Steam shovels; Construction workers; Construction equipment; Steam shovels; Construction workers; Construction equipment; Steam shovels; Fiction